Nineteenth-century religion, literature and society.
1 online resource
Keywords: Part of a four-volume set, this first volume looks at 'Traditions', offering an overview of the different religious traditions and denominations present in Britain during this period. The complete four-volume historical resource provides new opportunities for investigating the relationship between religion, literature and society in Britain and its imperial territories by making accessible a diverse selection of harder-to-find primary sources. These include religious fiction, poetry, essays, memoirs, sermons, travel writing, religious ephemera, unpublished notebooks and pamphlet literature. Spanning the long nineteenth century (c.1789-1914), the resource departs from older models of 'the Victorian crisis of faith' in order to open up new ways of conceptualising religion.